Pengaruh Internal Audit dan Efektivitas Pengendalian Internal Terhadap Kemampuan Deteksi Kecurangan (Fraud) pada Perguruan Tinggi Indonesia - irsutami irsutami; Anggy Ryansyah (Politeknik Negeri Batam, 2023)
The object of this learn was to evaluate the impact of internal audit and the efficiency of internal control on the capacity to identify fraud in Indonesian vocational institutes. Purposive sampling was utilized in this study's quantitative methodology, which included a literature review and questionnaire survey of 62 vocational institutions with internal supervisory units (SPI). Data analysis techniques use klasik assumptions, whereas an analysis of regressed liners using the SPSS V26 package is used for hypotheses testing. Based on the findings of statistical analysis, it was discovered that the variable of internal control effectiveness has a significant impact on the capacity to detect fraud in Indonesian universities, whereas the variable of internal audit does not. The outcomes of parallel testing show that the efficacy of internal control and internal audit both have a substantial impact on the capacity to identify fraud in Indonesian vocational institutes